CHRONOAMPEROMETRY AT CHANNEL ELECTRODES - THEORY OF DOUBLE ELECTRODES - Compton, R; Coles, B; Fisher, A (1994)
A theoretical treatment is presented which permits the computation of transient effects at double-channel electrodes. In particular, the current response of a downstream "detector" electrode to a potential step at an upstream "generator" electrode is established, and it is shown that such experiments can provide unique information both about the homogeneous behavior of electrogenerated species and about interfacial reactions occurring at the solid/liquid interface which forms part of the wall of the flow cell between the two electrodes. © 1994 American Chemical Society.